INSPIRATION FOR SMOKING AMONG MEDICAL STUDENTS OF ABBOTTABAD, PAKISTAN - Lodhi, Fahad Saqib; Farooqui, Rehan; Noor, Muhammad Munir; Irum, Saadia (Journal of Ayub Medical College Abbottabad, 2015)
Background: Doctors are the best person to persuade their patients to quit smoking. Trend of smoking among young doctors is increasing day by day. The present study was conducted to observe the source of inspiration and smoking trends among medical students. Methods: An observational study was conducted through a self-administered questionnaire from medical students of Ayub Medical College Abbottabad. Results: A total of 230 students participated in this study and out of these 210 were males and 20 were females. Forty-eight students (20.86%) started smoking at the age of less than 15 years and 143 students (62.17%) started smoking between the age of 15-20 years and 39 students (16.95%) started smoking after 20 years of age. A total of 147 students (63.91%) were inspired by their friends, 32 (13.91%) by media, 39(16.95%) by family members. Out of these 230 students 87 students (37.82%) smoked more than 10 cigarettes per day and 143 students (62.17%) smoked less than 10 cigarettes per day. Conclusion: Most of students started smoking at young age and their friends were source of inspiration. Keywords: Medical Students Smoking Source Of Inspiration